Myopia and glaucoma - Risk assessment - Bogdanova, Irina (Macedonian Association of Anatomists and Morphologists, 2017)
Glaucoma, a leading cause of irreversible blindness among the older population worldwide, is progressive optic neuropathy. The primary objective of this study is to evaluate the connection of the myopia with glaucoma. The other purposes, which is expected to be determined during the examination are: whether a certain type to myopia, presents a greater risk factor for the occurrence of glaucoma, from the other; also , to evaluate the degree of glaucoma changes compared to the amount of the myopia. The study is case-control study, in which are involved patients aged 25-70 years, with refractive anomaly myopia. The study is carried out of the University clinic for eye diseases, in Skopje, in the Cabinet for glaucoma. We examined 20 patients with refractive anomaly myopia, of which 8 patients are diagnosed as glaucoma and 12 patients without glaucoma. In all patients were made investigations: rate pressure, visual field, gonioscopy, ultrasound and biometry, OCT. From the obtained results can be determined as following: regarding the visual sharpness (with and without correction), patients who have myopia and glaucoma have a lower visual acuity, compared to patients who have myopia. There is no significant difference compared to ocular pressure between the two groups, as a result of the therapy that patients with glaucoma use. Characteristic of the results is the examination of the thickness of retinal layer of nerve fibers. This thickness is noticed between the two groups of patients. More than half of patients with myopia without diagnosed glaucoma, have thinner RNFL, which represents one of the primary findings to diagnose the glaucoma treated. The extent of damage which causes glaucoma, depends on the time of its detection. Later diagnosed glaucoma, will cause greater suffered damages. That is the reason why they are effort to highlight the need, in all patients in whom will be diagnosed myopia, to be implemented investigations for glaucoma detection, in order to prevent timely the damages of the nerve and retina.
Keywords: myopia; glaucoma; assessment; risk factors